The state of sleep and the current brain paradigm - Pigarev, Ivan N.; Pigareva, Marina L. (Frontiers in Systems Neuroscience, 2015)
Up to the present time cerebral cortex was considered as substrate for realization of the highest psychical functions including consciousness. Cortical sensory areas were regarded as structures specialized for processing of information coming from one particular modality (visual, auditory, somatosensory, and so on). However, studies of cortical activity in sleep-wake cycle demonstrated that during sleep the same neurons in the same cortical areas switch to processing of signals coming from the various visceral systems. After awakening these visceral responses disappear and the neurons return to processing of the information coming from the exteroreceptors. These observations indicate that most likely cortical areas are universal processors, which perform particular operations with incoming information independent of its origin. During wakefulness, results of the information processing on the cortical level should be directed to structures connected with organization of behavior and consciousness, while during sleep cortical outputs should be redirected to structures performing integration of the visceral information. Thus, results of sleep studies indicate that current brain paradigm should be changed.